Farmed Fish Market in Svay Rieng Town, Svay Rieng Province - Mardy Serey; Chhun Hong; Chanthorn Thoeung; Chanthona Prak; Leat Phai (MultiTech Publisher, 2023)
The fisheries sector in Cambodia plays an important role in the economic, security, food, and nutrition sectors, including freshwater, seawater, and aquaculture. This study aims to 1) understand the type and size of farmed fish in Svay Rieng town, 2) understand the farmed fish market chain in Svay Rieng town, and 3) analyze the economic efficiency of selling farmed fish in Svay Rieng town. As a method, a survey was conducted by selecting 40 samples (fish vendors) from Veal Yun Market and Rong Bonler Market in Svay Rieng town by face-to-face interviewing. The results found that the activities of selling and consumption of farmed fish in the market are very active. Fish vendors sold many types of farmed fish. The fish types that the vendors sell the most are channa striata, clarias macrocephalus, channa micropeltes, red tilapia, pantius gorionothus, puntioplites, and other types. The fish market chain in Svay Rieng town is traded and trafficked from brokers to traders and fish vendors in the market and resold to wholesalers, retailers, and consumers. For the economic efficiency analysis of farmed fish sales in Svay Rieng town, there is a majority of vendors who are prosperous. To encourage local fish farming, the government should step up its efforts to support farmers who raise fish as a family and those who depend on fishing for their livelihood by educating and training them to cut back on imports.